1998
DOI: 10.1086/301903
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Carrier Risk Associated with Common BRCA1 and BRCA2 Mutations in Ashkenazi Jewish Breast Cancer Patients

Abstract: Based on breast cancer families with multiple and/or early-onset cases, estimates of the lifetime risk of breast cancer in carriers of BRCA1 or BRCA2 mutations may be as high as 85%. The risk for individuals not selected for family history or other risk factors is uncertain. We determined the frequency of the common BRCA1 (185delAG and 5382insC) and BRCA2 (6174delT) mutations in a series of 268 anonymous Ashkenazi Jewish women with breast cancer, regardless of family history or age at onset. DNA was analyzed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
97
2
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(108 citation statements)
references
References 22 publications
7
97
2
2
Order By: Relevance
“…Studies of breast cancer patients have indicated that it may be difficult to define mutation screening criteria among women with minimal or no family history (Malone et al, 1998). Furthermore, the carrier risks associated with the mutations may be highly variable, and population-based risk estimates have indicated much lower cancer risks than those obtained from multiplecase families and, therefore, lower predictive value of cancer for a positive mutation test result (Struewing et al, 1997;Fodor et al, 1998;Thorlacius et al, 1998;Warner et al, 1999). Accordingly, genetic screening would be of greatest benefit in families with high cancer risk, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of breast cancer patients have indicated that it may be difficult to define mutation screening criteria among women with minimal or no family history (Malone et al, 1998). Furthermore, the carrier risks associated with the mutations may be highly variable, and population-based risk estimates have indicated much lower cancer risks than those obtained from multiplecase families and, therefore, lower predictive value of cancer for a positive mutation test result (Struewing et al, 1997;Fodor et al, 1998;Thorlacius et al, 1998;Warner et al, 1999). Accordingly, genetic screening would be of greatest benefit in families with high cancer risk, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, genetic screening would be of greatest benefit in families with high cancer risk, i.e. strong family history (Fodor et al, 1998), and a high probability of harbouring a BRCA1 or BRCA2 mutation. For this study, we chose families with a defined family history, and developed a model by which likelihood of carrying a BRCA1 or BRCA2 mutation can be estimated for each family separately.…”
Section: Discussionmentioning
confidence: 99%
“…The estimated lifetime risk of developing breast cancer for BRCA1/2 mutation carriers (carriers) varies between 30 and 80% [1][2][3][4][5][6]. Reasons for variation may include different mutations in the same gene (allelic variation) [5,[7][8][9], the effect of modifying genes [10][11][12], and non-genetic modifiers [13].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, these mutations occur at a rate of about 2.5% among the general Jewish Ashkenazi population (Struewing et al, 1995(Struewing et al, , 1997Roa et al, 1996;Fodor et al, 1998).…”
mentioning
confidence: 99%